The Implementation of Thought Stopping and Cognitve Restructuring Counseling Techniques to improve victim’s of relationship abuse Psychological Well-Being - Fahrurrazi Fahrurrazi; Haris Munandar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The aim of this report is to share findings in subject’s psychological condition and the effectiveness of thought stopping techniques by using thought stopping and cognitive restructuring techniques to change subject’s behavior by reducing irrational and intrusive thought as a means to help victim quality of life. The research methods was single case study and observation with an individual, age 27, male. Results shows that thought stopping and cognitive restructuring techniques during counseling session were effective to change subject’s behaviour. This findings supports the idea of thought stopping as a techniques able to help victim’s of relationship abuse psychological well-being.